Northern Chinese dental ages estimated from southern Chinese reference datasets closely correlate with chronological age. Issue 12 (December 2016) - Wong, Hai Ming; Wen, Yi Feng; Jayaraman, Jayakumar; Li, Jing; Sun, Ling; King, Nigel Martyn; Roberts, Graham J.
Abstract: While northern and southern Chinese are genetically correlated, there exists notable environmental differences in their living conditions. This study aimed to evaluate validity of the southern Chinese reference dataset for dental age estimation applied to northern Chinese. Dental panoramic tomographs of 437 northern Chinese aged 3 to 21 years were analysed. All the left maxillary and mandibular permanent teeth plus the 2 third molars on the right side were scored based on Demirjian's classification of tooth development stages. Mean and standard error of dental age were obtained for each tooth development stage, followed by random effect meta-analysis for mean dental age estimation. Validity of the method was examined through measures of agreement (95% limits of agreement, standard error of measurement, and Lin's concordance correlation coefficient) and measure of reliability (Intraclass correlation coefficient). On average, the estimated dental age overestimated chronological age by only around 1 month in both females and males. The Intraclass correlation coefficient values were 0.99 for both sexes, suggesting excellent reliability of the method. Reference dataset for dental age estimation developed on the basis of southern Chinese was applicable for use among the northern Chinese.